COMPLICAÇÕES CARDIOVASCULARES E REABILITAÇÃO PÓS COVID-19: UMA REVISÃO INTEGRATIVA (Fiep Bulletin - online, 2024)
ABSTRACTAlthough COVID-19 was initially recognized as a respiratory disease, it has the capacity to damage multiple associated organs due to the complex pathophysiological process of the disease and the need for prolonged hospitalization in severe cases. Although the greatest harmful outcomes affect individuals who progress to severe COVID-19, patients who develop the moderate form of the disease and who do not require hospitalization may also present a certain level of functional impairment. Cardiovascular complications in the post-acute period of COVID-19 are frequently observed in patients recovering from COVID-19. Objective: To verify the impacts of post-COVID-19 sequelae, possible cardiovascular complications and scientific evidence of post-COVID-19 rehabilitation. Methods: This is an integrative review of the literature, in the MEDLINE, LILACS, PubMed, SciELO databases, published between 2020 and 2023. The study sample consists of 15 studies. Results: Studies have shown that post-COVID-19 patients present different sequelae, some more frequently, without a clinical pattern; observing the multisystemic scope, there was an advance in the rehabilitation process, with significant effects on the evolution of initial clinical conditions. Conclusion: Post-COVID-19 rehabilitation is a key component for the reintegration of individuals into society. Considering the multisystemic manifestations of the post-infection condition, rehabilitation services must consist of a multidisciplinary team, including the physical education professional, to meet all the demands of patients until their functional capacity is reestablished. Keywords: COVID-19, cardiovascular complications in COVID-19, sequelae, post-COVID-19, post-COVID-19 rehabilitation.